WAGE DIFFERENTIALS BY FIRM SIZE: THE EFFICIENCY WAGE TEST IN A DEVOLOPING COUNTRY - Isabel Raposo; Tatiane Menezes (European Regional Science Association (ERSA), 2011)
Using data from the Brazilian Labor Monthly Survey (PME/ IBGE) for the years of 2006 and 2007, the paper investigates if the wage differential by firm size in Brazil can be explained by the predictions of the Efficiency Wage Theory. It is adopted a Switching Regression Model to estimate if large size companies pay a higher wage premium for dispended labor effort, as compared to smaller enterprises. The results proved the EW predictions. Besides the positive relation between effort and wage differentials by firm size, the results also showed that such wage differences favors larger firms, as compared to smaller ones, because they tend to remunerate better more skilled employees with long term contracts.
Keywords: 330